ANALYSIS OF THE ROLE OF MICROFINANCE AT BANK SYARIAH MANDIRI TO THE DEVELOPMENT OF MICRO, SMALL BUSINESS CUSTOMERS, AND MEDIUM (MSMES) (CASE STUDY ON ISLAMIC BANKS INDEPENDENT KCP. GUNUNG TUA, PADANG REGENCY NORTH OLD) - mulya mulya; armyn hasibuan; adanan murrah (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Financing is the provision of capital from the financing party to parties who need capital to run a business. In general, MSMEs rely on their own capital in running their businesses, and they are usually trapped by loan sharks, given the low accessibility to formal sources of financing. Every year the MSME business unit in Indonesia develops from 2017 to 2018 because the data available at the ministry of cooperatives and small and medium enterprises is managed from the Central Statistics Agency (BPS 2019) data from 2017 to 2018. MSMEs in the Padang Lawas area North 2020 is still classified as stagnant, it's just that it has decreased in its income from the average government-programmed restructuring proposal of 50-75 percent. With the Bank Syariah Mandiri KCP. Gunung Tua is expected to be able to help people or customers who need micro-financing for the development of businesses run by customers, for example street vendors, handicrafts, souvenir businesses and other businesses. This study aims to determine how the role of Bank Syariah Mandiri in the business development of MSME customers. This type of research is qualitative research, while the data collection techniques in this study use documentation observation and interviews. As for the data analysis technique in this study, the process of systematically searching and compiling the data obtained. From the research results it is known that the role of microfinance in Bank Syariah Mandiri KCP. Gunung Tua in developing MSME businesses greatly affects the increase in customer business income.